Data Walks as a Participatory Research Process: Examining Inequality and Social Issues in the American South - Jessica Sperling; Adrian Brown; Brynne Townley; Goharik Tigranyan; Megan O'Sullivan (Journal of Participatory Research Methods, 2025)
The American South has a long history of race-based social and economic inequity. Despite making progress, systemic inequities persist, highlighting the need for region-based inquiry to understand the complexities of challenges in key policy areas affecting the region. Specifically, community engaged research can provide voice to community members, thereby providing historical and contemporary context to fully understand the challenges and sources of inequity and develop community-appropriate solutions to address them. In recent years, research across sectors has included a focus on community engaged research, including participatory action research, which focuses on collaboration and equitable participation of residents and local partners from the community. A community data walk provides an interactive mechanism for community members to engage with data on key issues affecting their community and participate in and lead the interpretation of results. In this way, data walks represent one potential tool for participatory action research. Yet, there is relatively little published information on the process of developing and implementing a data walk. This paper describes data walk processes across a set of three convenings focused on social issues in the American South. It describes the rationale for the data walks, their development and implementation, and the knowledge gained from these data walks. It also addresses key lessons from data walk implementation that can inform others looking to develop similar work. Overall, this work provides added guidance on ways to enact community engaged research and generate community-researcher co-production of knowledge through data walks.